Ecology & Its Applications in Local Architecture (Journal of University of Babylon for Engineering Sciences, 2019)
The theories of interaction with the environment, considered as the most important and efficient theories currently in use, especially in the local urban environment, which has become far from the interaction with the environment. From here, we note that there is a lack of knowledge about the simulation of the performance of the interaction with the local environment through a computer model in order to achieve thermal comfort for users and rationalize the use of local environmental resources. Therefore, the research presents a theoretical framework for the definition of feasibility, its potential and its applications in an attempt to reduce the gap between technological development in the world, especially in the possibilities of simulating interaction with the environment, and the local reality. It also provides a practical framework through the application of computer simulations based on the analysis of a set of theories and to find the efficiency of its performance. This application is based on the creation of a virtual model of a multi-story building before and after the application of computer simulation and trying to achieve better thermal comfort values ​​for the occupants of the building through the use of a certain programs, most notably (Rhino, Grasshopper, RayMan). The results showed the efficiency of using computer simulation programs to achieve better thermal value for the occupants. The research led to the development of a local multi-storey building that is climate efficient by following the design mechanisms derived from the climate of the region and thus achieving a climatic environment with optimal performance according to the comfort standards Thermal.